PENERAPAN MODEL PEMBELAJARAN PROBLEM-BASED HYBRID LEARNING DALAM PENCAPAIAN LITERACY DIGITAL SISWA - Restami, Made Prima; Sugiani, Komang Anik (STKIP PGRI Situbondo, 2025)
Digital literacy is a very important issue in today's era. This study aims to analyze the Problem-Based Hybrid Learning Model in the achievement of students' digital literacy. This study uses a literature review by participating in the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA). Article searches were conducted in research journal databases by taking from Elsevier, Pubmed, Science Direct, Web of Science, National Index, and Google Scholar. The results of this study are based on the results of a review of 15 articles that found that the use of P-BHL in the learning process at school and in college has a positive impact such as improving performance, comprehension, critical thinking skills, digital literacy skills and cognitive abilities in learning by applying the P-BHL learning method both at school and in college.